(Co)oxidation/cyclization processes upon irradiation of triphenylamine - Bonesi, Sergio Mauricio (2014)
Abstract. Irradiation of triphenylamine (Ph3N) in nitrogen-flushed solution leads to 9-phenylcarbazole and two tetrahydroderivatives (1,2,3,4- and 1,2,7,8-) via disproportionation of the corresponding 4a,4b-dihydrocarbazole. In oxygen-equilibrated solution oxidative cyclization occurs through the intermediacy of a triplet peroxy diradical, which either abstracts a hydrogen atom intramolecularly or (mainly) cleaves back to the reagents. The role of the key intermediates is supported by DFT calculations and by trapping by triarylphosphines (that are thus efficiently oxidized, while preventing the cyclization of Ph3N). The hydroperoxide, on the other hand, causes inefficient co-oxidation of sulfides.